Multiple Andreev reflection in a two-dimensional topological insulator - Apostolov, S. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The electronic transport at the edge of a two-dimensional topological insulator between two superconducting electrods is determined by multiple Andreev reflections. We propose a model of such transport with regard for both Andreev and normal reflections at the contact and the electron- electron-impurity scattering at the edge. Based on this model, we calculate the distribution functions and define the features resulting from these phenomena. The results allow one to determine experimentally the ratio of the contributions of the normal reflection from the superconducting contact and the electron-electron-impurity scattering on the edge affecting the quantum electron transport in a topological insulator.